Clinical and Biochemical Factors of Portosystemic Encephalopathy in Cirrhosis - Himayat Ullah, Muhammad Ashraf, Raza Ullah, Shahida Na, Jawad Ashraf, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Responsible factors in patients with portosystemic encephalopathy and their relation with the severity of encephalopathy using “west haven scoring”. Methods: This cross-sectional study was done in the Gastroenterology Department, Hayatabad Medical Complex Peshawar. After ethical approval, a sample of 500 patients was calculated by universally accepted sample calculators. 95% confidence intervals and 5%margin of error. The sample was taken by a non-probability consecutive sampling technique. Results: Out of 500 patients, 307 were male and 193 females. The mean age was 57.36(±17.65 SD). Electrolyte imbalance (79.2%) was the most prevalent responsible factor, followed by infection (47.4%) and dehydration (24.4%). The number of patients with Grade 1, 2, 3 and 4 encephalopathy were 48, 187, 223, 42 respectively. In the majority of patients with encephalopathy, more than one responsible factor was present. Conclusion: Portosystemic encephalopathy is one of the most serious and life-threatening complications of liver failure and cirrhosis.